Interference from the vertical variation of soil phosphorus and from water stress on growth in maize, the soybean and sunflower (Revista Ciência Agronômica, 2017)
The distribution of phosphorus (P) in the soil interferes with the availability of the nutrient and can affect plantgrowth. The aim of this study was to compare the growth and accumulation of P in maize, soybean and sunflower plants invertical gradients of the nutrient in the soil, with and without water stress. The design was completely randomised with fivereplications, in a 3 x 2 factorial scheme: three soil depth gradients of P (decreasing, increasing and nil) and two conditions ofsoil water availability (with and with no water stress). The depth gradients of P were in decreasing doses of P2O5(300, 200,100 and 0 mg dm-3), increasing doses (0, 100, 200 and 300 mg dm-3) and equal doses (150 mg dm-3) applied to the intermediatelayers between 0.0-5.0, 5.1-10.0, 10.1-15.0 and 15.1-20.0 cm. Height, dry weight and P accumulation in the roots and shootswere quantified. The data were submitted to analysis of variance, and mean values compared by Tukey’s test (p